Role of doping in probe microscopies for the Si(111) 7×7 surface - Dingxin Fan; Yuki Sakai; James R. Chelikowsky; Daniel Meuer; Alfred J. Weymouth; Franz J. Giessibl (Physical Review Research)
We investigate a scanning probe microscopy image flickering phenomenon, i.e., distinct changes in intensity with the tip height, observed on a B-doped Si(111) 7×7 reconstructed surface. The phenomenon is exclusively observed in heavily doped systems owing to large variations in the adatom heights (∼0.5 a.u.) and the existence of bistable subunits upon doping as the probe tip approaches the surface. We find that B atoms prefer to reside in the surface layer, which is ∼1.1 eV more stable compared to interior layers. These dopant atoms exert a substantial influence on the structural integrity and electronic structure of the lattice.